Ampliação vocabular: glossário de textos do livro didático de língua portuguesa "Vontade de saber português" do 9º ano - Assunção, Célia Davi de (2015)
This research aimed to verify the vocabulary difficulties faced by 9th year students while understanding the didactic book of Portuguese Language (DBPL) “Vontade de Saber Português”, used at the Municipal School Sebastião Rangel. We noticed the students had some doubts concerning the unknown vocabulary in the texts and, therefore, in text comprehension. The hypothesis is that one “difficult” word and the lexicon used by DBPL author can disturb student comprehension. We adopted some action which could simplify the little vocabulary understanding and contributed to extend it. For that reason, the job was theoretically based on Biderman (1999), Barbosa (1989), Dias (2004), Krieger (2012), Coelho (1993) and on National Curriculum Parameters of Portuguese Language, aiming to ally theory and practice. The application methodology of the proposal was done in order to the students understand that the word needs to be adapted to its context. At the begging of the job, the students read the texts and took notes of the “difficult” words, selecting, corpus. We analyzed the doubts, registering them. Then, we showed to the students the classification of abbreviated words after each entry. The students separated the words for grammar classes – lexical words” (KRIEGER, 2012). Such words have a very significant meaning to the comprehension of the read texts, being interesting to take a look in online dictionaries. In the creative glossary, done by the students, the words were spread in alphabetical order. They transcript the part where was the word and copied again, substituting the word to a clearer word. Finally, we asked the students a writing production using five words from the glossary; we showed them that the meaning of the words is not found only in the dictionary, but they can be used in different contexts. In the analyzes, was discovered that there is one necessity of a pedagogic didactic work more effective with elementary school lexicon. Thus, this proposal is not a closed receipt, but the infield location allowed a reflexive pedagogic practice about lexicon education.